Typical and atypical magnetic resonance imaging appearances of primary cardiac lymphoma - Ibrahim, Rositaa Mohd; Noh, Mohamad Syafeeq Faeez Md; Nor, Mohamad Arif Muhammad; Sari, Nor Ashikin Md; Bahari, Norafida; Rahim, Ezamin Abd; Mohammed, Yusri (Asian Society of Cardiovascular Imaging, 2017)
Primary cardiac lymphoma (PCL) accounts for 1.3% of all cardiac tumours. Diagnosis is particularly challenging owing to its rarity and non-specific presentation. Although transthoracic echocardiogram is the initial imaging modality used to detect cardiac masses, advances in cardiac magnetic resonance imaging (CMR) has allowed more detailed assessment, which enables accurate diagnosis and subsequent therapy. We would like to highlight two cases of PCL that were diagnosed in our institution, manifesting with typical and atypical CMR features.